Discovery of Selenocysteine as a Potential Nanomedicine Promotes Cartilage Regeneration With Enhanced Immune Response by Text Mining and Biomedical Databases - Ye, Jing; Xu, Bingbing; Fan, Baoshi; Zhang, Jiying; Yuan, Fuzhen; Chen, Yourong; Sun, Zewen; Yan, Xin; Song, Yifan; Song, Shitang; Yang, Meng; Yu, Jia-Kuo (Frontiers in Pharmacology, 2020)
Unlike bone tissue, little progress has been made regarding cartilage regeneration, and many challenges remain . Furthermore, the key roles of cartilage lesion caused by traumas, focal lesion, or articular overstress remain unclear. Traumatic injuries to the meniscus as well as its degeneration are important risk factors for long-term joint dysfunction, degenerative joint lesions, and knee OA a chronic joint disease characterized by degeneration of articular cartilage and hyperosteogeny . Due to the limited inherent self-repair capacity of cartilage lesion, the Biomaterial drug-nanomedicine is considered to be a promising alternative. Therefore, it is important to elucidate the gene potential regeneration mechanisms and discover novel precise medication, which are identified through this study to investigate their function and role in pathogenesis. Methods: We downloaded the mRNA microarray statistics GSE117999, involving paired cartilage lesion tissue samples from 12 OA patients and 12 patients from a control group. First, we analysed these statistics to recognize the differentially expressed genes (DEGs). We then exposed the gene ontology (GO) annotation and the Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway enrichment analyses for these DEGs. Protein- protein interaction (PPI) networks were then constructed, from which we attained eight significant genes after a functional interaction analysis. Finally, we identified a potential nanomedicine attained from this assay set, using a wide range of inhibitor information archived in the Search Tool for the Retrieval of Interacting Genes (STRING) database. 66 DEGs were identified with our standards for meaning (adjusted P- value < 0.01, |log2 - FC| ≥1.2). Furthermore, We identified eight hub genes and one potential nanomedicine - Selenocysteine based on these integrative data. We identified eight hub genes that could work as prospective biomarkers for the diagnostic and biomaterial drug treatment of cartilage lesion, involving the novel genes CAMP, DEFA3, TOLLIP, HLA-DQA2, SLC38A6, SLC3A1, FAM20A and ANO8. Meanwhile, these genes were mainly associated with immune response, immune mediator induction and cell chemotaxis. Significant support is provided for obtaining a series of novel gene targets, and we identify potential mechanisms for cartilage regeneration and final nanomedicine immunotherapy in regenerative medicine.